SYSTEM DYNAMICS MODEL OF HIERARCHICAL RELATIONSHIPS BETWEEN SOCIO-ECONOMIC SUBJECTS - Vasilii M. Kartvelishvili; Dmitriy S. Krynetskiy; Eduard A. Lebedyuk (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
In this article authors develop a system dynamics model in which a real process of hierarchical interaction between managing and managed subjects of socio-economic relationship is shown with the example of manager and employee. Authors focus on employee motivation and discuss mainstream motivation theories. Additionally authors use the model to provide an analysis of how different factors affect efficiency, employee salary and the relationship between manager and employer. Authors examine the effects different sets of factors have on employee-manager dynamic in time.